A polycrystalline SiO2 colloidal crystal film with ultra-narrow reflections. Issue 34 (31st March 2015) - Fu, Qianqian; Chen, Ang; Shi, Lei; Ge, Jianping
Abstract : This work reported a high quality photonic crystal film with an ultra-narrow photonic bandgap obtained via a chemical synthetic route. Abstract : This work reported a high quality photonic crystal film with an ultra-narrow photonic bandgap obtained via a chemical synthetic route. The bandgap is much narrower than that of traditional colloidal crystals, which makes the film qualified for use in optical devices. The narrow PBG originates from not only the high crystallinity and uniform orientations of microcrystals within the film but also the very close refractive indices between the silica and the polymer matrix. Due to the matching of the refractive index, the amorphous contents of the film are optically transparent and do not interfere with the reflection, so that the photonic crystal film is tolerant of the existence of disordered contents.